Investigation of Persistence Value as a Study Protection Factor among Health Care Organizer Students - Dinyáné Szabó, Marianna; Pusztai, Gabriella (European Journal of Mental Health, 2017)
Introduction: To be successful, serious commitment, willingness of being involved in education and learning (on the part of the students), and (on the part of the education institution) demand for high standard are required. One of the most important determinants of student achievement is persistence, the research of which has now been in the focus of international investigation.Objective: The authors investigated variables affecting students- persistence value (e.g. attendance at lessons, parents- religiousness, use of the Internet, sports, etc.) among students starting their health care studies.Method: The students participating in the survey were - as mentioned - the first year (BSc) students specialising in health care organisation at the Public Health Care Departments of Semmelweis University, the University of Debrecen (and Nyíregyháza) (N = 200 persons).Results: 1. By using GLZ regression (Likelihood Ratio Chi-Square = 115.688, df = 13, p = 0.000), the explanatory variables - that most influence the value of the persistence variance - were filtered. (i) E.g. Attendance at the lessons, Extra rewards, Sports, Parents- Religiousness, Community Membership are of positive effect. (ii) The use of Internet has a negative impact in the model. 2. Cluster analysis was used to produce student groups from the predictor variables.Conclusion: Examining students- persistence values can help university faculties, the teachers to see, who will succeed in their studies, and who need increased help to evolve and develop their mental potentials.